Understanding Mental Health: What Are the Issues for Black and Ethnic Minority Students at University? - Jason Arday (Social Sciences, 2018)
Black and Minority Ethnic (BME) communities continue to experience inequalities within the United Kingdom (UK) mental health system despite major government policy initiatives. Access to higher education for many ethnic minorities remains problematic. Within higher education, BME students consistently face barriers in terms of accessing culturally appropriate services including a lack of cultural understanding, communication issues, and where and how to seek help. This paper attempts to address the problems facing ethnic minorities with regard to accessing mental health services at university. Importantly, this paper highlights that barriers to accessing mental health support for ethnic minorities directly impact upon attainment outcomes and psychological well-being. This study utilizes the narratives of 32 BME university students to examine the impact of negotiating racial inequality and discrimination at university and the impact upon mental health. Aspects examined considered the impact of belonging, isolation, and marginalization on mental health and how this consequently affects university participation for BME students. Utilizing a thematic analysis paradigm, the key findings presented point towards differential healthcare outcomes for ethnic minority university students experiencing mental illness. The empirical findings in this paper suggest that currently ethnic minority service users experience overt discrimination and a lack of access to culturally appropriate services that are cognizant of the racialized plights faced by BME individuals. These findings inform an overarching dialogue, which suggests that mental health service providers need to work more collegially with people from BME communities prior to service design and delivery. Furthermore, the findings suggest that, upon presenting mental health issues, information should be made available in appropriate languages for ethnic minorities to support understanding about their illnesses and how they can seek professional intervention and help. Conclusions and recommendations provided advocate greater diversification of mental health support systems for ethnic minority students within universities. Conclusions drawn will also consider how existing systems can function to dismantle racial inequality within the mental health profession.